Problems of Quality Assurance in Managing the Environment in Russian Cities - Sergey Kirillov (European Regional Science Association (ERSA), 2011)
Transport and industrial enterprises are the reasons for the basic pollution of the environments of large cities. This problem is particularly acute in Russia, where strict environmental standards either do not exist or are not enforced. Improving the management of ecological and economic system of urban environmental resources usage is largely dependent on functional type of the city and the number of people inhabiting it. In this context, the author distinguishes the following urban areas: Capital (Moscow); Major regional centers of Russia, including St. Petersburg; Multifunctional cities; Medium-sized cities with one or two city-forming enterprises; County towns and other settlements. The author proposes a model for designing an economic mechanism of environmental management in large cities depending on management methods used at the present time, their ecological and economic efficiency and possibility of including new management tools into the mechanism. During the modeling of ecological-economic mechanism of urban land use it is necessary to choose a rational variant of regulative instruments which will lead the system of urban land use to the expected form. According to the author, there are three aims that could be achieved in the cities: reducing pollution, improving the stability of the system, increasing the profitability of the land due to optimization of its usage. The aims are interrelated but the local authorities must define in what direction the land affairs will develop. The combination of specific tools in ecological-economic mechanism of urban land use determines the features of urban environment and quality of life. The usage of market and administrative management tools of the urban land use mechanism changes the economical system, the environment, the transportation system, urban landscape and the structure of urban area zoning.
Keywords: 330